EFEKTIFITAS NEGOSIASI DALAM PROSES KOMUNIKASI POLITIK - Andriansah; Harmonis (UKRI, 2024)
This research investigates the effectiveness of negotiations in the context of the political communication process in general. Involving an in-depth analysis of political negotiation situations, this research aims to identify the key factors that influence the success of negotiations and their impact on the political communication process. Using an interdisciplinary approach that combines political communication theory and negotiation strategy, this research provides insight into how effective negotiation skills can improve results in reaching political agreements. The findings of this research contribute to the practical and theoretical understanding of the importance of negotiation in achieving political goals and provide guidance for improving negotiation skills in complex political communication contexts.